Socio-Cultural Factors and the Utilization of Antenatal Care Services in Budaka Health Centre IV, Budaka District - Esther Sabano (Uganda Christian University, 2024)
This Research study was conducted at Budaka Health Centre IV in District Local Government in Eastern Uganda. The study was intended to investigate the factors affecting the utilization of antenatal care services in Budaka Health Centre IV, Budaka District. In the study, Maternal health education was taken as the independent variable while utilization of antenatal care services as the dependent variable. Doctors, Clinical officer, Nurses, mothers, and other health staffs provided primary data for the study. The research was mostly qualitative in nature, with minor mathematics used. The study adopted a cross sectional survey design. The sampling techniques included purposive sampling for Doctors and clinical officers and simple random for Nurses and mothers. In order to gather data, questionnaires were issued to clinical officers and doctors whereas mothers and other staff were interviewed. To analyze the collected data, quantitative methods were used to establish frequencies and percentages. Qualitative means were also used whereby themes and quotations were made. The researcher carried out the study by physically interviewing Health workers, mothers and group employees etc. The data collected by research assistants and the researcher were put together for analysis and the analysis was brought out in chapter four. Chapter five covers mostly summary discussion of finding, conclusions, and recommendations by the researcher. Key findings of the study revealed that educated pregnant women utilise antenatal care services, they are aware and knowledgeable of the services of antenatal care services and the easily access antenatal care services. The biggest challenge faced was the inadequate funding. This can be addressed if a fee called research emergency is introduced. This can facilitate the smooth management of the exercise. The study recommends that Outreaches should be set in all the villages to operate on a weekly basis to allow the pregnant mothers who come from very far to access antenatal care services at a nearby place.